The expression and regulation of HOX genes and membrane proteins among different cytogenetic groups of acute myeloid leukemia. Issue 9 (2nd July 2020) - Wang, Huili; Lin, Sheng‐Yan; Hu, Fei‐Fei; Guo, An‐Yuan; Hu, Hui
Abstract: Background: The cytogenetic aberrations were considered as markers for diagnosis and prognosis in acute myeloid leukemia (AML), while the expression and regulation under different cytogenetic groups remain to be fully elucidated. Methods: In this paper, for favorable, poor, and cytogenetically normal groups of AML patients, we performed comprehensive bioinformatics analyses including identifying differentially expressed genes (DEGs) and microRNAs (miRNAs) among them, functional enrichment and regulatory networks. Results: We found that DEGs were enriched in membrane‐related processes. Eleven genes and two miRNAs were significantly differentially expressed among these three AML groups. In survival analysis, membrane‐related genes and several miRNAs were significant on prognostic outcome. Notably, six HOXA and three HOXB genes were significantly in low expression and high methylation in AML with favorable cytogenetics. Meanwhile, the miRNA‐HOX gene co‐regulatory networks revealed that HOXA5 was a hub node and regulated an AML oncogene SPARC . Conclusion: Our work may provide novel insights to the molecular characteristics and classification between AML with different cytogenetics. Abstract : We integrated comprehensive bioinformatics analyses for genes between favorable, poor and cytogenetically normal (CN) groups of acute myeloid leukemia (AML) patients. We found that differentially expressed genes were enriched in membrane related processes. Eleven genes and two microRNAs were significantly differentially expressed among these 3 AML groups. Six HOXA and three HOXB genes was significantly in low expression and high methylation in AML with favorable cytogenetics.